Developmental foundations of physiological dynamics among mother–infant dyads: The role of newborn neurobehavior. Issue 4 (11th April 2022) - Gao, Mengyu (Miranda); Speck, Bailey; Ostlund, Brendan; Neff, Dylan; Shakiba, Nila; Vlisides‐Henry, Robert D.; Kaliush, Parisa R.; Molina, Nicolette C.; Thomas, Leah; Raby, K. Lee; Crowell, Sheila E.; Conradt, Elisabeth
Abstract: This study tested whether newborn attention and arousal provide a foundation for the dynamics of respiratory sinus arrhythmia (RSA) in mother–infant dyads. Participants were 106 mothers ( M age  = 29.54) and their 7‐month‐old infants (55 males and 58 White and non‐Hispanic). Newborn attention and arousal were measured shortly after birth using the NICU Network Neurobehavioral Scale. Higher newborn arousal predicted a slower return of infant RSA to baseline. Additionally, greater newborn attention predicted mothers' slower return to baseline RSA following the still‐face paradigm, and this effect only held for mothers whose infants had lower newborn arousal. These findings suggest that newborn neurobehavior, measured within days of birth, may contribute to later mother–infant physiological processes while recovering from stress.